Measuring the Statistical Capacity of Nations - Cameron, Grant J.; Dang, Hai-Anh H.; Dinc, Mustafa; Foster, James; Lokshin, Michael M. (World Bank, Washington, DC, 2019)
The international development community has used the World Bank's Statistical Capacity Index since its inception in 2004. The Sustainable Development Goals create new challenges for national statistical systems to produce high-quality and internationally comparable data. This paper reviews measurement methodologies, posits desired attributes, and presents theoretical and empirical frameworks for the new, improved index to monitor progress in the statistical capacity of nations. The paper illustrates the properties of the updated index with global data from 2016.